Formation and Development of State Migration Policy - JUSSUPOV, Murat; BOZHKARAULY, Altai; RUSTEMBEKOVA, Dinara (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018DO - 10.14505//jarle.v9.5(35).16, 2018)
The article discusses the main national documents in the field of state regulation of migration processes in the Republic of Kazakhstan. A number of regulatory legal acts on the regulation of migration processes were studied, such as: the Law of the Republic of Kazakhstan ‘On Migration of the Population’, the Concept of the Migration Policy of the Republic of Kazakhstan.